Synthesis of (–)-Virginiae Butanolide A (VB-A) - Donges, Jonas; Frank, Andrea; Schollmeyer, Dieter; Nubbemeyer, Udo (Synthesis, 2023)
The 2-(1′-hydroxyalkyl) paraconyl alcohols (–)-VB-A and (–)-SCB-5 are known as highly active signaling molecules within antibiotics production in Streptomyces sp. These γ-butyrolactone type compounds are epimeric at the 1′-OH-group. A direct synthesis of (–)-VB-A from (–)-SCB-5 that uses a late-stage inversion of the 1′-hydroxy group is not favored because of side reactions of the carbinol in β-position to the lactone C=O function. Therefore, an orthogonally protected 1,4-diol incorporating the central syn/anti 1′,2,3-stereotriad as described within the (–)-SCB-5 synthesis was used as an advanced intermediate to generate (–)-VB-A, too. A combination of protecting group operations and a 1′-OH group inversion via oxidation and diastereoselective reduction delivered the anti/anti 1′,2,3-stereotriad. Final transformations related to that as described for (–)-SCB-5 enabled completion of the (–)-VB-A-synthesis.
Keywords: bioactive γ-butyrolactone; diastereoselective synthesis; defined stereotriad; OH-group inversion; oxidation reduction sequence; iodocyclization; ozonolysis